Analysis Of The Effect Of Content Marketing And Influencer Marketing On Purchase Intention Toward The Noera Beauty Brand With Product Knowledge As An Intervening Variable - Khofifah, Raudhotul; Albari, Albari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the influence of content marketing and influencer marketing on consumer purchase intention toward the Noera Beauty brand, with product knowledge as an intervening variable. The research aims to understand how digital marketing strategies contribute to shaping consumer perceptions and encouraging purchasing decisions. A quantitative approach was employed by distributing an online questionnaire to 165 respondents who had been exposed to Noera Beauty promotional content on social media. Data were analyzed using a structural equation modeling approach to evaluate direct and indirect relationships among variables. The results indicate that both content marketing and influencer marketing positively affect purchase intention, both directly and indirectly through product knowledge. Furthermore, product knowledge serves as a significant mediating factor that enhances the effectiveness of digital marketing strategies in driving purchase intention. These findings highlight the strategic importance of informative content and credible influencers in improving consumer understanding and trust, ultimately strengthening interest in purchasing. This research provides valuable insights for marketers in designing more effective digital strategies within the competitive beauty industry.